2014
DOI: 10.1037/a0036630
|View full text |Cite
|
Sign up to set email alerts
|

When is irony effortful?

Abstract: Whereas some studies indicate that ironic—as opposed to literal—readings of utterances take longer to process, others indicate that the 2 are processed at comparable speeds. We propose that mindreading processes are at least partly responsible for the mixed results, as we present 3 experiments that include stories having a target utterance with either an Ironic or Literal reading. Experiment 1 replicates earlier findings (Spotorno, Koun, Prado, Van Der Henst, & Noveck, 2012) showing that ironic readings take l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 36 publications
5
40
1
Order By: Relevance
“…The interpretation of a metaphor or of an ironic statement requires a listener to go beyond the literal meaning of an utterance and to take into consideration other possible interpretations (Clark & Gerrig, 1984; R. J. Gibbs & Gerrig, 1989; Grice, 1975; Sperber & Wilson, 1986; Spotorno & Noveck, 2014). Figurative language is arguably a more complex case of pragmatic inference that requires additional world knowledge beyond the literal linguistic utterance as well as metarepresentational skills (Gildea & Glucksberg, 1983; Sperber & Wilson, 2008; Wilson & Sperber, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of a metaphor or of an ironic statement requires a listener to go beyond the literal meaning of an utterance and to take into consideration other possible interpretations (Clark & Gerrig, 1984; R. J. Gibbs & Gerrig, 1989; Grice, 1975; Sperber & Wilson, 1986; Spotorno & Noveck, 2014). Figurative language is arguably a more complex case of pragmatic inference that requires additional world knowledge beyond the literal linguistic utterance as well as metarepresentational skills (Gildea & Glucksberg, 1983; Sperber & Wilson, 2008; Wilson & Sperber, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been suggested that pragmatic intrerpretation depends on a Theory of Mind (ToM), the cognitive component that is responsible for ascribing mental states (e.g., beliefs, intentions) to oneself and/or to others and for interpreting the behaviour of others based on these mental states. Again, experimental evidence has shown that ToM-related processes (e.g., taking into account speaker's reliability or knowledge) are involved during online pragmatic interpretation (see e.g., Breheny, Ferguson & Katsos, 2013;Grodner & Sedivy, 2011;Spotorno & Noveck, 2014) and that successful pragmatic understanding in children may depend on the development of a Theory of Mind (Filippova, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a typical experiment, participants would be presented with scenarios that would end in an utterance that could be interpreted as either literal or sarcastic. On the one hand, evidence from self-paced reading studies (e.g., Giora, 1995; Giora, Fein, & Schwartz, 1998; Spotorno & Noveck, 2014), and eye-tracking studies (e.g., Filik & Moxey, 2010; Kaakinen, Olkoniemi, Kinnari, & Hyönä, 2014) showing that sarcasm comprehension takes longer than literal language comprehension, has been taken to support modular accounts. Other evidence showing that sarcasm can be comprehended as fast as literal language, again from self-paced reading (e.g., Gibbs, 1986), and additionally from visual-world paradigm studies (e.g., Kowatch, Whalen, & Pexman, 2013), has been taken as support for more interactive accounts.…”
Section: Empirical Evidencementioning
confidence: 99%